Clinical characteristics of allergic bronchopulmonary aspergillosis. (15th January 2020) - Zhang, Cuiping; Jiang, Zhilong; Shao, Changzhou
Abstract: Background: Allergic bronchopulmonary aspergillosis (ABPA) is an allergic pulmonary disease caused by a hypersensitivity reaction to Aspergillus colony in the airways. Due to the diversity of disease manifestations and physicians' incomplete knowledge of ABPA, patients with ABPA are often misdiagnosed and given poor prognosis. Objectives: To investigate the clinical characteristics, treatment and prognosis status among patients with ABPA. Methods: We retrospectively analyzed 75 patients diagnosed as ABPA in Zhongshan Hospital, Fudan University between October 2008 and June 2018. Results: Among 75 patients, 28% had asthma as the predisposing condition and 69% suffered from misdiagnosis before ABPA diagnosis was made, among which 21% were misdiagnosed as tuberculosis. About 34% of patients had eosinophil count below 500 cells/μL and 25% had total serum IgE level <1000 IU/mL. Nearly half of patients did not meet the diagnostic criteria of ABPA and all the patients who overlapped with invasive pulmonary aspergillosis (IPA) did not meet the diagnostic criteria of standard ABPA. Patients who did not fully meet the diagnostic criteria were more likely treated with inhaled corticosteroids (ICS) and antibiotics, but more difficult to attain response and remission and easier to develop advanced ABPA. Conclusions: This study demonstrates an unsatisfactory situation of diagnosis, treatment and prognosis of ABPA, including a high misdiagnosis rate, uncertainty in the diagnosis of ABPA, lack of standardization in treatment and relatively poor prognosis.